Crop pollination services: Complementary resource use by social vs solitary bees facing crops with contrasting flower supply. Issue 3 (5th November 2020) - Bänsch, Svenja; Tscharntke, Teja; Gabriel, Doreen; Westphal, Catrin
Abstract: Many farmers are facing high economic risks if pollinator declines continue or temporal and spatial variation in wild bee communities cause reduced pollination services. Co‐flowering crops might compete for pollinators, while they also might facilitate the delivery of pollination services. This rarely studied topic is of particular interest with respect to the foraging decisions of bees from different functional groups and when more sparsely and mass‐flowering crops are in bloom at the same time. The abundance of honey bees, bumble bees and solitary bees in strawberry fields was quantified with transect walks along a gradient of oilseed rape (OSR) availability (product of OSR land cover and temporally changing OSR flower cover). We established a pollination experiment with pollination treatments (open‐, wind‐ and self‐pollination) to study the effects of insect pollination on strawberry fruit weight and quality. Changes in OSR availability exhibited contrasting effects on social versus solitary bees in strawberry fields. Bumble bees and honey bees were less abundant in strawberry fields when OSR availability was high, whereas solitary bees were facilitated. With more strawberry flowers, we found more bees in general. When flowers were open‐pollinated, they resulted in heavier fruits with better commercial grades compared to wind‐ and self‐pollinated flowers. A higher bee abundance enhanced the strawberry fruit weight and quality but depended on flower order and variety. Synthesis and applications . Sparsely flowering crops may compete with mass‐flowering crops for social bee pollinators, while solitary pollinators in the field might be evenly facilitated. To ensure best fruit weight and quality, it can be beneficial to support bee abundance in the field. While some social and solitary bee species can be managed for pollination services, wild bees, in particular solitary species, should be conserved and promoted for stable crop pollination services in dynamic agricultural landscapes. Abstract : Sparsely flowering crops may compete with mass‐flowering crops for social bee pollinators, while solitary pollinators in the field might be evenly facilitated. To ensure best fruit weight and quality, it can be beneficial to support bee abundance in the field. While some social and solitary bee species can be managed for pollination services, wild bees, in particular solitary species, should be conserved and promoted for stable crop pollination services in dynamic agricultural landscapes.